53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0156
|View full text |Cite
|
Sign up to set email alerts
|

Plasma assisted combustion: kinetic studies and new combustion technology

Abstract: The recent progresses in plasma assisted low temperature combustion, in-situ Mid-IR diagnostics, and kinetic mechanism development are presented. The observations of plasma and ozone activated new flame regimes such as the self-sustaining cool diffusion flames, cool premixed flames, and mild combustion are reported. The direct measurements of intermediate species and the kinetic pathways of low temperature ethylene oxidation in a non-equilibrium plasma reactor are presented. The recent development and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…[17][18][19][20] In nonequilibrium plasmas, the electron temperature is significantly higher and the plasma is kinetically active due to new reaction pathways enabled by electron collisions. 21 Consequently, non-equilibrium plasmas are superior for some combustion applications in various ways, for example, NOx emission treatments, 13,15,16 Low Temperature Combustion (LTC), 22,23 shortening ignition time, [24][25][26] generation of volumetric ignition with increased heat release rates, [27][28][29] stabilization of lean and turbulent flames 14,30,31 and on-board fuel reforming. [32][33][34] The superiority is attributed to the new reaction pathways introduced by the energetic electrons of the nonequilibrium plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] In nonequilibrium plasmas, the electron temperature is significantly higher and the plasma is kinetically active due to new reaction pathways enabled by electron collisions. 21 Consequently, non-equilibrium plasmas are superior for some combustion applications in various ways, for example, NOx emission treatments, 13,15,16 Low Temperature Combustion (LTC), 22,23 shortening ignition time, [24][25][26] generation of volumetric ignition with increased heat release rates, [27][28][29] stabilization of lean and turbulent flames 14,30,31 and on-board fuel reforming. [32][33][34] The superiority is attributed to the new reaction pathways introduced by the energetic electrons of the nonequilibrium plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of plasma actuator to improve MILD combustion has been investigated. Wada et al [31] and Ju et al [32] found that the reforming of a portion of a CH 4 /air mixture at the exit of the fuel jet into intermediate species and the resultant flow perturbations caused by the large density gradient have significant impacts on the ignition delay and the mixing process. Mardani and Khanehzar [33] showed that applying the plasma discharge to the flame region leads to an intensification of the reaction zone, increment of heat release rate by a factor of 3, and 30% reduction of flame liftoff.…”
Section: Introductionmentioning
confidence: 99%
“…Τα δύο µέτωπα κινούνται προς το εσωτερικό του θαλάµου καύσης στα δεξιά µε το µέτωπο χαµηλής θερµοκρασίας να αποµακρύνεται από το κύριο µέτωπο. Ενδεικτικό του διπλού µετώπου φλόγας είναι το προφίλ 5 της θερµοκρασίας στο Σχήµα 7.2αʹ 1 H διεξαγωγή της προσοµοίωσης έγινε ως εξής: Λόγω του µεγάλου µεγέθους του µηχανισµού χηµικής κινητικής εφαρµόστηκε η Correlated Dynamic Adaptive Chemistry and Transport µέθοδος, (CO-DACT) [180,181], σε συνδυασµό µε τη Hybrid Multi-Timescale µέθοδο (HMTS) [182]. Συγκεκριµένα, οι σχετικοί µειωµένοι µηχανισµοί και οι σχετικές ιδιότητες της µεταφοράς υπολογίστηκαν µε δυναµικό τρόπο, χρησιµοποιώντας τη µέθοδο CO-DACT.…”
Section: η διαδικασία της ανάφλεξηςunclassified